Direct Quantification of mRNA and miRNA from Cell Lysates Using Reverse Transcription Real Time PCR: A Multidimensional Analysis of the Performance of Reagents and Workflows - Ho Y.K. (Public Library of Science (PLoS), 2018)
10.1371/journal.pone.0072463